Analisis Dampak Implementasi Transfer Pricing Dan Dualisme Kewenganan Terhadap Investor Perusahaan Manufaktur Di Kota Batam - Serli Diovani Teza; Handra Tipa (JURNAL AKUNTANSI BARELANG, 2019)
This research uses descriptive and qualitative methods. The purpose of this study is to analyze and impact of implementation of transfer pricing and dualism of authority to the investors of manufacturing companies in Batam. transfer pricing is the transfer of goods and services of capital and intangible that occur between multinasional group company that are geographically located in differen counties. The implementation of transfer pricing is very highbecause it is driven by technological developments and the complexity of problem in the city of batam which is a factor prone to the decline in the investment climate. Transfrer pricing This is a serious problem for the country because it directly affects the amount of aggregate income countries. although the general tax directorate has arranged all related to transfer pricing but the implementation has not gone well in accordance with the government policy for the average companies tend to pursue lower taxes. The results of study show that the impact of implementation of transfer pricing and dualism of authority to investors manufacturing companies in the city of Batam more negative impacts that positive impact. 1) investor are more interested in investing in countries with low tax rates .2) the number of excess spillover goods exspor that is not accommodate in Singapore and malalaysia goods are taxless entry into Indonesia so as to benefit investors. 3) Dualism of authority to make investor confused so that many investor out of the city of Batam, the number of unemployed increase steadily from year to year.